2019
DOI: 10.1111/nep.13577
|View full text |Cite
|
Sign up to set email alerts
|

Use of patient‐reported outcome measures and patient‐reported experience measures in renal units in Australia and New Zealand: A cross‐sectional survey study

Abstract: Aim Patient‐reported outcome measures (PROMs) and patient‐reported experience measures (PREMs) are increasingly used in research to quantify how patients feel and function, and their experiences of care, however, knowledge of their utilization in routine nephrology is limited. Methods The Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) PROMs working group conducted a prospective cross‐sectional survey of PROMs/PREMs use among renal ‘parent hospitals’. One survey per hospital was completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…A recent prospective cross-sectional survey of 79 dialysis units in Australia and New Zealand showed that 55 of 79 units (70%) collected PROMs or patient-reported experience measures. 14 The Integrated Palliative Outcome Scale-Renal (IPOS-Renal) was the most commonly reported instrument to measure symptoms (40% of units) and the EQ-5D-5L for the assessment of quality of life (24%). Insufficient time and staff resources were identified as the main barriers to collection of PROMs (19 out of 24 units (79%)).…”
mentioning
confidence: 99%
“…A recent prospective cross-sectional survey of 79 dialysis units in Australia and New Zealand showed that 55 of 79 units (70%) collected PROMs or patient-reported experience measures. 14 The Integrated Palliative Outcome Scale-Renal (IPOS-Renal) was the most commonly reported instrument to measure symptoms (40% of units) and the EQ-5D-5L for the assessment of quality of life (24%). Insufficient time and staff resources were identified as the main barriers to collection of PROMs (19 out of 24 units (79%)).…”
mentioning
confidence: 99%
“…Such services should as a priority, according to renal clinicians, include symptom management given the well‐established significant symptom burden and resulting poor quality of life in patients with advanced renal disease 17‐19 . A recent cross sectional study described the utility of patient reported symptom measures used to directly inform clinical care in Australia and New Zealand and 65% of renal units routinely measured symptoms for patients with advanced renal disease 20 . Embedding consistent metrics of symptom measurement for patients in renal supportive care services could provide collaborative patient and service outcomes and research opportunities to improve understanding of how RSC improves quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various outcomes can provide insight into health‐care quality and should be taken into account when evaluating hospital performances. Nowadays, patient‐reported outcomes (PROs; eg, health‐related quality of life [HRQOL] and symptom burden) are considered important health‐care outcomes and PRO measures (PROMs) are increasingly being implemented into routine care, including nephrological care 10‐13 . Therefore, the logical next step is to include PROs—in addition to clinical outcomes—in the process of health‐care quality evaluation.…”
Section: Figurementioning
confidence: 99%
“…For example: the hospital rates depicted in are increasingly being implemented into routine care, including nephrological care. [10][11][12][13] Therefore, the logical next step is to include PROs-in addition to clinical outcomes-in the process of health-care quality evaluation. However, incorporation of PROs and using funnel plots for PROs is accompanied with additional challenges.…”
mentioning
confidence: 99%